2009
DOI: 10.1007/s00128-008-9497-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Risk Assessment of Trace Metal Pollution in Surface Water from Yangtze River in Nanjing Section, China

Abstract: In order to investigate the contamination levels of trace metals, surface water samples were collected from six regions along Yangtze River in Nanjing Section. The concentrations of trace metals (As, B, Ba, Be, Cd, Cr, Cu, Fe, Pb, Li, Mn, Mo, Ni, Sb, Se, Sn, Sr, V and Zn) were determined using inductively coupled plasma-atomic emission spectrometry (ICP-AES). Total concentrations of the metals in the water samples ranged from 825.1 to 950.4 microg/L. The result was compared with international water quality gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(174 citation statements)
references
References 20 publications
10
148
2
Order By: Relevance
“…The hazard quotients (HQs) estimated for local residents are summarized in Table 4 based on oral consumption and dermal absorption of water. It can be seen that the non-carcinogenic risk of HQ in (hazard quotient of ingestion exposure) was far higher than that of HQ d (hazard quotient of dermal absorption), which is in line with the findings of other investigations (e.g., Wu et al 2009). The total HQ values of heavy metals Hg and Cr(VI) were smaller than unity in all the districts of the Wei River, suggesting that the concentrations of these metals may pose little or no health threat to the local residents.…”
Section: Spatial Distribution Of Hpi In the Wei Riversupporting
confidence: 86%
“…The hazard quotients (HQs) estimated for local residents are summarized in Table 4 based on oral consumption and dermal absorption of water. It can be seen that the non-carcinogenic risk of HQ in (hazard quotient of ingestion exposure) was far higher than that of HQ d (hazard quotient of dermal absorption), which is in line with the findings of other investigations (e.g., Wu et al 2009). The total HQ values of heavy metals Hg and Cr(VI) were smaller than unity in all the districts of the Wei River, suggesting that the concentrations of these metals may pose little or no health threat to the local residents.…”
Section: Spatial Distribution Of Hpi In the Wei Riversupporting
confidence: 86%
“…Many large-scale electronic and machinery industries have entered into this region (Xu et al 2009) and plenty of metallic pollutants were probably released into water environments, which potentially contribute to the high level of some metals and constant variation of the concentrations. However, a previous study (Wu et al 2009b) showed that there was no spatial difference among the total concentrations of 19 metals in six sampling sites of Yangtze River at Nanjing Section.…”
Section: Non-carcinogenic Risk Induced By the Metalsmentioning
confidence: 88%
“…Wu et al (2009b) quantified 19 metals in Yangtze River at Nanjing section and found that Fe was of the highest concentration. In China, about 36% of steel is produced in the Yangtze River Basin, which might contribute to the high level of Fe in the surface water of this region.…”
Section: Concentration Of Metals In Source Watersmentioning
confidence: 98%
“…Exposure of human being to metals could occur via three main pathways including direct ingestion, inhalation through mouth and nose, and dermal absorption through exposures skin; however, ingestion pathway is the most significant for drinking water (Miguel et al 2007;USEPA 2004;Wu et al 2009). The dose received through the pathway considered was determined using Eq.…”
Section: Risk Assessment On Human Healthmentioning
confidence: 99%